Planejamento tributário como instrumento de gestão empresarial - Lopes, Maria Cristina Godinho (2000)
The laws that compose the effective tributary system in Brazil were interpreted withthe objective ofdemonstrating when and in which circumstances there is legality or illegahty in the practices oftax planning adopted by the Brazilian taxpayers. Several applied interpretation methods were used together, in agreement with the case and with the values implicit inthe law. The analysis of the legislation allowed to verify that the Brazilian judicial system allows any taxpayer the possibility to plan their businesses ina way not to pay, to reduce in a significant way thetax burden oreven postponing the payment ofsome tributes attheir convenience. The legal fiscal economy is called tax avoidance. To be legal it is necessary that the action or the taxpayer*s omission be previous to the beginning of the tributary obligation and that the acts are not practiced as fraud or simulation. The economy obtained through illegal means is called tax evasion. It usually occurs after the beginning ofthe tributary obligation and/or resulting from theuseofconsent vices as a resuít, errors, coercion, simulation or fraud.